KEEFEKTIFAN PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA KAHOOT UNTUK TOPIK PERSAMAAN KUADRAT PADA SISWA KELAS X SMA IPH 2 SURABAYA - Alfa Charisma Sardjono Pello (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2018)
This research was conducted in class X of IPH 2 High School Surabaya. Researcher looked at several problems in the classroom, namely: the ability of students to understand less quadratic equations, lack of learning tools that are good for use in classrooms, activities in class that seem unattractive to improve learning motivation and the condition of students who are always individual in achieving success. To support this, this research is assisted by kahoot media. This research is a type of experiment that begins with the development of a 4D model device. Based on the problems above, the researcher helps the teacher by developing learning tools that are well validated. After that, the researcher will check the effectiveness of the device and then be implemented in the experimental class in order to obtain good learning outcomes. Descriptive data analysis results, obtained valid learning tools, good teacher ability, positive student response, and student activities that are in a good range. The results of inferential data analysis obtained an average increase in learning outcomes in the experimental class is greater than the average increase in learning outcomes in the control class. Learning tools in the form of RPP, LKS, and THB developed with the 4-D development model are valid tools to support learning effectively so that student learning outcomes are better than student learning outcomes that are taught using conventional learning. Key Word: effectiveness, cooperative learning, teams games tournament, quadratic equations, kahoot media